Analysis of modern pollen data from the prairies of central North America - Morris, Christopher J. (Kansas State University, 2013)
Fossil pollen assemblages are widely used in paleoenvironmental reconstruction of vegetation regimes and climate conditions. The modern analog technique (MAT) is a popular method used for analysis of these fossil pollen assemblages, but a large modern pollen dataset, such as the North American Pollen Database (NAPD), is needed to provide modern comparisons for interpretation of analog/no-analog situations. While many climate types are well represented within the NAPD, the climates of the southern and central Great Plains of North America are poorly represented. In this study, I collected 31 sediment samples containing pollen from these underrepresented climate types across the Great Plains in the U.S.A. Analysis of these 31 pollen assemblages, along with 504 samples classified as “prairie” from the NAPD and 24 pollen samples from the Flint Hills of Kansas, U.S.A. was conducted to determine if the three major prairie types (short grass, mixed grass, and tallgrass prairies) could be delineated from pollen records alone. Two different MAT dissimilarity metrics (Squared Chord Distance and Canberra Distance Metric) were assessed for their ability to delineate among prairie types and Squared Chord Distance (SCD) was found to a be the better prairie type classifier than Canberra Distance Metric (CDM). Receiver Operator Characteristic (ROC) curve analysis was used to assess the ability of each metric to identify similar pollen assemblages. It has been show in previous studies that two genera found in this region – Ambrosia and Artemisia –respond to temperature and moisture availability in different ways. Using the ratio of the proportions of Ambrosia and Artemisia pollen grains in a pollen assemblage it was found that tallgrass prairies are significantly different from the other two prairie types. The Ambrosia/Artemisia ratio is also useful in determining climatic conditions. This ratio provides paleoenvironmental researchers with a simple quantitative tool to quickly assess general climatic conditions and prairie type.
Keywords: Pollen; MAT; Prairies; Great Plains; Geography (0366)